What are the key barriers for the further development of shale gas in China? A grey-DEMATEL approach - Dong Wei; Hongyuan Liu; Kai Shi (Energy Reports, 2019)
The evaluation and analysis of barriers that restrict the large-scale development of shale gas are beneficial to the selection of a scientific and reasonable development model. The objective of our study was to reveal the key barriers to the large-scale development of shale gas in China. Sixteen barriers were identified by adopting literature reviews and expert interviews, and the grey-based Decision-Making Trial and Evaluation Laboratory (grey-DEMATEL) approach was adopted to analyze the barriers based on the sample data obtained from a questionnaire of senior experts in China's shale gas industry. The results showed that high development costs, lack of experience, lack of technology transfer between enterprises, risk of environmental pollution, lack of key technologies, and lack of capability in investment and risk resistance are the key barriers to the further development of shale gas in China. We put forward some policy suggestions based on these results.
Keywords: 330; Evaluation; Barriers; China; Grey-DEMATEL; Large-scale development; Shale gas